Romiplostim as a Therapeutic Intervention for Tacrolimus-induced Immune Thrombocytopenia in a Pediatric Cardiac Transplant Patient. Issue 6 (August 2021) - Gipson, Daniel R.; Larkin, Trisha; Seifert, Robert; Black, L. Vandy
Abstract : Tacrolimus-induced immune thrombocytopenia (ITP) is a rare entity that can occur years after initiation of tacrolimus therapy following solid organ transplantation, and platelet recovery can be substantially delayed following discontinuation of tacrolimus. Romiplostim, a thrombopoietin receptor agonist approved by the FDA in 2018 for the treatment of chronic ITP in children, may be a useful therapy to hasten platelet recovery in the acute ITP setting in place of immunomodulating agents. We present a case of tacrolimus-induced ITP successfully treated with romiplostim in a child following cardiac transplantation.